2005
DOI: 10.1089/thy.2005.15.718
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Disease and Increased Cardiovascular Risk

Abstract: The effects of thyroid dysfunction are thought to be reversible on restoration of euthyroidism, but postmortem and epidemiologic data suggest that subclinical or treated thyroid disease is associated with increased vascular risk. In order to determine the extent of this risk, and to explore whether the nature and/or treatment of thyroid disease are critical in this relationship, we used medical record linkage to match patients with treated thyroid disease of various etiologies with routinely collected national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 29 publications
4
79
1
1
Order By: Relevance
“…Refs, References. criteria (case-control or cohort studies) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Following review, studies were excluded because of an overlap with subjects from other studies (16,19,20); because reviews were not providing original data (12,13,22); due to inclusion of very few (n!10) hyperthyroid individuals to meaningfully allow calculation of the mortality risk (23,25); because of lack of overall mortality data (17); based on inclusion of a control group that was also hyperthyroid (30); or, finally, because evaluation of thyroid status was solely based on serum TSH (21) (Fig.…”
Section: Selection and Characteristics Of The Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Refs, References. criteria (case-control or cohort studies) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Following review, studies were excluded because of an overlap with subjects from other studies (16,19,20); because reviews were not providing original data (12,13,22); due to inclusion of very few (n!10) hyperthyroid individuals to meaningfully allow calculation of the mortality risk (23,25); because of lack of overall mortality data (17); based on inclusion of a control group that was also hyperthyroid (30); or, finally, because evaluation of thyroid status was solely based on serum TSH (21) (Fig.…”
Section: Selection and Characteristics Of The Studiesmentioning
confidence: 99%
“…1). Details of the remaining eight (14,15,18,24,(26)(27)(28)(29) studies on which our review is based are shown in Table 1.…”
Section: Selection and Characteristics Of The Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in cardiovascular risk after RAI treatment has also been suggested. [12][13][14] However, Metso and colleagues found that hypothyroidism post-RAI offered protection from cardiovascular disease, suggesting that hyperthyroidism per se rather than RAI treatment is responsible for the increased cardiovascular events in these patients.…”
Section: Radioactive Iodinementioning
confidence: 99%
“…1 GD patients have normal thyroid hormone production and discharge but the physiological demands of body are not normal resulting in increased levels of thyroxin (T4) and tri-iodothyronine (T3) in blood. 2 This excessive T4 and T3 production results in goiter, palpitations and increased cardiovascular risk (classical symptoms of hyperthyroidism) 3 along with anxiety, heat intolerance, hand tremor, insomnia, hair loss, hyperactivity, excessive sweating, itching, weight loss regardless of increased appetite, frequent defecation, diarrhoea, muscle weakness, palpitations, and skin warmth and moistness in GD patients. 2,4 Certain risk factors including gender, age, stress, smoking, elevated concentrations of TSH, T3 and T4 in blood are known to affect the rate of GD.…”
Section: Introductionmentioning
confidence: 99%